Experimental parametric study on the effect of diameter and number of bars on the cyclic performance of bar damper - Ghaedi, Khaled; Javanmardi, Ahad; Ibrahim, Zainah; Rashid, Raizal; Gordan, Meisam; Khatibi, Hamed (Elsevier Ltd, 2025)
This paper studies the effect of the diameter and number of bars on the cyclic behavior of the bar damper (BD). A BD is a metallic damper made of several steel bars welded between the bottom and top anchor plates. The energy dissipation mechanism of the BD primarily depends on the flexural yielding deformation of the bars under either unidirectional or bi-directional loads. To achieve this aim, seven specimens were tested with four different diameters of bars and four different numbers of bars. A series of quasi-static cyclic loading tests were performed on the BD specimens in the laboratory. In addition, a comparative study of all the geometrical parameters of the BD, including the height of the BD was performed. The experimental results showed that all BD specimens exhibited stable hysteretic behavior and low yield displacement. The BD specimen demonstrated a damping ratio of 34 %-41 % and a ductility range of 27–69. The results of the comparative analysis concluded that the height of the bars mainly affects the yield displacement, ultimate displacement and cumulative displacement of the damper, while the diameter and number of bars affect the yield force and ultimate force of the damper.